The Effect of Inflation Rate, BI Rate, and Income Per Capita of Indonesia on Spread Based Income of Conventional Banking Sector in 2014-2023 - Christie, Florencia; Hermanto, Florentina Elena; Kosasih, Valerie Angela; Huda, Aulia Nurul (Jurnal Riset Akuntansi dan Keuangan, 2024)
The banking industry is an important member of Indonesia’s economy as an intermediary that circulates the country’s money. The purpose of this study is to ascertain the effects of certain economic variables, namely, inflation, interest rate, and income per capita towards the banking industry’s main source of income known as spread based income. This study employs time series regression to analyze data collected from Bank Indonesia, Indonesia Banking Statistics, and Statistics Indonesia. The research provided results that indicate a positive yet insignificant relationship between inflation and spread based income, a negative and insignificant relationship between interest rate and spread based income, as well as a negative and significant relationship between income per capita and spread based income.